2010
DOI: 10.4161/cib.3.4.12093
|View full text |Cite
|
Sign up to set email alerts
|

Extraversion predicts individual differences in face recognition

Abstract: In daily life, one of the most common social tasks we perform is to recognize faces. However, the relation between face recognition ability and social activities is largely unknown. Here we ask whether individuals with better social skills are also better at recognizing faces. We found that extraverts who have better social skills correctly recognized more faces than introverts. However, this advantage was absent when extraverts were asked to recognize non-social stimuli (e.g., flowers). In particular, the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 23 publications
(29 reference statements)
9
71
5
Order By: Relevance
“…They may therefore reflect a common trait here, whereby stable and relaxed individuals are more accurate on the target-present trials of the face test than reactive and tense participants. This observation converges with previous reports of correlations between face recognition memory and anxiety (Mueller et al, 1979;Nowicki et al, 1979) or neuroticism (Bothwell et al, 1987;Li et al, 2010). In contrast to previous studies, these associations were found here with a face task that minimizes any memory demands.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…They may therefore reflect a common trait here, whereby stable and relaxed individuals are more accurate on the target-present trials of the face test than reactive and tense participants. This observation converges with previous reports of correlations between face recognition memory and anxiety (Mueller et al, 1979;Nowicki et al, 1979) or neuroticism (Bothwell et al, 1987;Li et al, 2010). In contrast to previous studies, these associations were found here with a face task that minimizes any memory demands.…”
Section: Resultssupporting
confidence: 92%
“…High anxiety, for example, seems to reduce individual face recognition performance (Mueller, Bailis, & Goldstein, 1979;Nowicki, Winograd, & Millard, 1979), and subjects are also more accurate under moderate than high arousal (Brigham, Maass, Martinez, & Whittenberger, 1983). There is also evidence that observers exhibiting high levels of extroversion and emotional stability are more accurate at face recognition than introvert and neurotic individuals (Li et al, 2010). These findings are somewhat inconclusive as others have failed to find a similar role for extroversion (Thompson & Mueller, 1984), but neuroticism does appear to produce a consistent negative impact on face recognition (Bothwell, Brigham, & Pigott, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Studies also show, that the detection of extraverted facial features depends also on the evaluator´s levels of extraversion and that extraverts are better at decoding social information than introverts [32]. We did not measure the levels of extraversion of our subjects in this study, therefore we can not proof this finding on our participants as well as to state, whether the worse recognition of extroverted features could be caused by the larger number of introverts in our sample.…”
Section: Discussioncontrasting
confidence: 50%
“…Indeed, Sergent (1984) suggests that configural encoding is what is disrupted by studies conducted on face perception are cross-sectional. There are significant individual differences in face recognition ability (Li et al, 2010), in the amount of holistic processing participants engage in (Wang, Li, Fang, Tian, & Liu, 2012), and in terms of how faces are encoded (Bobak, Parris, Gregory, Bennetts, & Bate, 2017;Mehoudar, Arizpe, Baker, & Yovel, 2014). This means that, potentially, effects reported in the literature are due to cohort effects which may be unduly influenced by individual differences in studies with relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 79%